Influence of metatarsophalangeal joint stiffness on take-off performances and lower-limb biomechanics in jump manoeuvres - Jia, S.-W.; Lam, W.-K.; Huang, Z.; Baker, J. S.; Ugbolue, U. C.; Gu, Y. (Journal of Sports Sciences, 2022)
Forefoot and toes are prominent regions for locomotion and individual metatarsophalangeal joint (MTPJ) stiffness may be linked to jump take-off mechanics and performances. However, little is known about the relationships between MTPJ stiffness and take-off related variables. This study examined the relationship between individual MTPJ stiffness and biomechanical variables under various vertical countermovement jumps (CMJ) conditions. We measured MTPJ stiffness on 21 male university basketball players and then asked them to perform jumps under single, consecutive and running CMJ conditions. Pearson`s correlation coefficient was employed to examine the relationships between MTP passive stiffness and each jumping performance, ground reaction force (GRF) and joint kinematic and kinetic variables. The results indicated that MTPJ stiffness significantly correlated with maximum jump height (r = 0.49, moderate), peak take-off velocity (r = 0.47, moderate), peak take-off ankle plantarflexion moment (r = 0.68, strong), peak dorsiflexion moment (r = 0.60, strong) and peak take-off ankle power (r = 0.44, moderate) in consecutive CMJ. Only a moderate correlation between MTPJ stiffness and peak MTPJ extension take-off velocity (r = -0.46, moderate) was determined in a single CMJ. There were no significant correlations found in running CMJ conditions. These findings imply that higher MTPJ stiffness of participants was related to improved jump performances in consecutive jumps.